Aerobic CO oxidation of a metal-bound carbonyl in a NHC-stabilized cobalt half-sandwich complex - Dürr, Simon; Zarzycki, Bartosz; Ertler, Daniel; Ivanovic-Burmazovic, Ivana; Radius, Udo (Organometallics, 2012)
The complexes [(η -C R )Co( Pr Im)(η -C H )] (R = H 1; Me 2) were synthesized in good yields via reaction of one equivalent of the N-heterocyclic carbene Pr Im (R Im = 1,3-dialkylimidazolin-2-ylidene) and the bis(ethylene) complexes [(η -C R )Co(η -C H ) ]. These complexes serve as convenient starting materials for chemistry using the [(η -C R )Co( Pr Im)] complex fragment. The reaction with carbon monoxide leads to the carbonyl complexes [(η -C R )Co( Pr Im)(CO)] (R = H 3; Me 4) in good to excellent yields. The carbonyl complexes 3 and 4 are very air sensitive and react readily with oxygen in the solid state and in solution. Whereas the cyclopentadienyl-substituted complex [(η -C H )Co( Pr Im)(CO)] (3) decomposes upon reaction with O to intractable products, [(η -C Me )Co( Pr Im)(CO)] (4) yields the structurally characterized cobalt(III) carbonato complex [(η -C Me )Co( Pr Im)(κ -CO )] (5). This reaction represents the first example of O oxidation of a metal-bound carbonyl for a 3d transition metal complex. The oxidation is too fast to be monitored by NMR spectroscopy, and application of low-temperature time-resolved UV/vis spectroscopy combined with stopped-flow techniques led to the detection of a possible intermediate. On the basis of these experiments and computational investigations using density functional theory (DFT) the peroxo acyl complex [(η -C Me )Co( Pr Im)(κ -C,O-COOO)] (B) is assumed to be the key intermediate detected. The DFT calculations further reveal that this reaction is strongly exothermic with two kinetic barriers, one for the exothermic addition of O to the carbonyl complexes 4 to give the peroxo acyl complex [(η -C Me )Co( Pr Im)(κ -C,O-COOO)] (B), the other for the rearrangement of B to give the carbonato complex [(η -C Me )Co( Pr Im)(η -CO )] (5). The key step for the rearrangement is the formation of CO in the coordination sphere of cobalt and the attack of metal-bound oxygen at the carbon atom of CO . © 2012 American Chemical Society.